Accomplishing food security through community based initiatives in Thrissur:A participatory analysis - Mridula N (Department of Agriculture, College of Horticulture, 2010)
Food security has become a matter of serious concern the world over. Recently in Kerala there is an increased emphasis on community-based organizations (CBO) as a means of increasing agricultural production and thereby food security. The study intended to appraise the nature and relative role of CBOs involved in ensuring food security, explore the extent of awareness of various stakeholders in agricultural development process and factors contributing to it, identify gaps in food grain production in a selected Grama Panchayat and assess possible interventions to ensure food security through community based initiatives. Observations on the basic details of CBOs included the details of members, year of start, production and market details, subsidiary enterprises, marketing of products, relation with local bodies, skills and aspirations of CBO members and difficulties encountered. The different constraints faced by the extension agents in implementing food security programmes were also noted. The awareness level of stakeholders on the different dimensions of food security concerns of the community was assessed. Farmers were found to have better awareness on production and nutrition dimension; CBO members had better awareness on the distribution and socio economic dimensions as well as food security as a whole. The extension agents had the least awareness on all the four dimensions. . Positive correlation between farmer’s awareness on food security and age was found and negative correlation was found between their awareness and sex. Negative correlation between age, farming experience and income of extension agents and awareness was observed. Significant, positive correlation between CBO member’s awareness and their age was noted. Positive correlation between awareness and their farm size and negative correlation between awareness and education were also observed . It was also found that negative correlation existed between awareness and farm size of the people’s representatives. A methodology for quick assessment of food requirement of a locality was developed through participatory method in Kuzhikany North watershed of Kodakara Panchayath. A synthesis of wealth ranking and survey and recall method was employed. The daily requirement of food grain, vegetables, pulses and tubers for individuals of each class was found out through memory recall method. This tool can be used in any place for rapid estimation of food requirement. The requirement and production of different food items in the above panchayath was found out and considerable difference was noted. The major policy implications of the findings of the study include reorientation of agricultural development planning on the basis of location specific food requirement, intensification of household production of vegetables and tubers, formulation of exclusive programmes for food security, standardizing the procedure for leasing out land in a participatory mode, and mediating the process of leasing out private paddy lands for food production. LSGIs should facilitate gender sensitive farm mechanization for CBOs to operate effectively in food security programmes and organise focused and customized programmes for building awareness on food security for all the stake holders.